The art of vaginal birth after caesarean section: a retrospective observational study - Varadaraju, Rani; Gopalan, Anusha H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: There is an alarming rise in caesarean section rate worldwide. Our study aims to highlight the factors contributing to successful vaginal birth after caesarean section (VBAC) in our institution over a period of 4 years. Methods: Our study is a retrospective observational study. 149 patients who underwent successful VBAC during the period of November 2022 to October 2024 were included in the study and their demographic characteristics, labor progress, maternal and neonatal outcomes studied. Results: Out of the total 149 patients, 91% of patients were admitted with spontaneous onset of labor pains. Admission Bishop’s score was >3 for 87% of patients. Majority of patients (95%) progressed in labour with low dose oxytocin. 7% of patients had gestation diabetes mellitus (GDM), 3% had gestational hypertension highlighting the fact that these are not contraindications for trial of labour after caesarean (TOLAC). There was no maternal and neonatal morbidity or mortality. Conclusions: With proper case selection, antenatal counselling and adequate pain relief - TOLAC can result in successful VBAC. VBAC is a safe alternative to elective repeat caesarean section in patients with one previous caesarean section. Increasing VBAC deliveries can reduce the overall caesarean section rate and reduce the morbidities associated with repeated caesarean sections.